A Carotenoid-Deficient Mutant in Pantoea sp. YR343, a Bacteria Isolated from the Rhizosphere of Populus deltoides, Is Defective in Root Colonization - Bible, Amber N.; Fletcher, Sarah J.; Pelletier, Dale A.; Schadt, Christopher W.; Jawdy, Sara S.; Weston, David J.; Engle, Nancy L.; Tschaplinski, Timothy; Masyuko, Rachel; Polisetti, Sneha; Bohn, Paul W.; Coutinho, Teresa A.; et al. (Frontiers in Microbiology, 2016)
The complex interactions between plants and their microbiome can have a profound effect on the health and productivity of the plant host. A better understanding of the microbial mechanisms that promote plant health and stress tolerance will enable strategies for improving the productivity of economically-important plants. Pantoea sp. YR343 is a motile, rod-shaped bacterium isolated from the roots of Populus deltoides that possesses the ability to solubilize phosphate and produce the phytohormone indole-3-acetic acid. Pantoea sp. YR343 readily colonizes plant roots and does not appear to be pathogenic when applied to the leaves or roots of selected plant hosts. To better understand the molecular mechanisms involved in plant association and rhizosphere survival by Pantoea sp. YR343, we constructed a mutant in which the crtB gene encoding phytoene synthase was deleted. Phytoene synthase is responsible for converting geranylgeranyl pyrophosphate to phytoene, an important precursor to the production of carotenoids. As predicted, the ΔcrtB mutant is defective in carotenoid production, and shows increased sensitivity to oxidative stress. Moreover, we find that the ΔcrtB mutant is impaired in biofilm formation and production of indole-3-acetic acid. Finally we demonstrate that the ΔcrtB mutant shows reduced colonization of plant roots. Taken together, these data suggest that carotenoids are important for plant association and/or rhizosphere survival in Pantoea sp. YR343.